Molecular mechanisms of resistance to BRAF and MEK inhibitors in BRAFV600E non–small cell lung cancer. (June 2020) - Facchinetti, Francesco; Lacroix, Ludovic; Mezquita, Laura; Scoazec, Jean-Yves; Loriot, Yohann; Tselikas, Lambros; Gazzah, Anas; Rouleau, Etienne; Adam, Julien; Michiels, Stefan; Massard, Christophe; André, Fabrice; et al.
Abstract: Introduction: BRAF is a confirmed therapeutic target in non–small cell lung cancer (NSCLC), as the BRAF inhibitor dabrafenib, in combination with the MEK inhibitor trametinib, is approved for the treatment of NSCLC harbouring BRAF V600E mutation. Scant evidence is available concerning the mechanisms of resistance to BRAF/MEK inhibitors in BRAF V600E NSCLC. Patients and methods: Patients with BRAF V600E NSCLC with acquired resistance to BRAF/MEK inhibitors were included in the institutional, prospective MATCH-R (from "Matching Resistance") trial and underwent tumour and liquid biopsies at the moment of radiological progression. Extensive molecular analyses were performed, including targeted next-generation sequencing (NGS), whole-exome sequencing (WES), RNA sequencing and comparative genomic hybridisation (CGH) array. Results: Of the 11 patients included, eight had progressed on dabrafenib-trametinib combination, two on dabrafenib monotherapy and one on vemurafenib (BRAF inhibitor). Complete molecular analyses were available for seven patients, whereas an additional case had only targeted NGS and CGH array data. Among these eight patients, acquired molecular events potentially responsible for resistance were detected in three who progressed on dabrafenib-trametinib combination, that is, MEK1 K57N, RAS viral (v-ras) oncogene homolog ( NRAS ) Q61R and rat sarcoma viral oncogene homolog ( KRAS ) Q61R mutations. One patient progressing on dabrafenib monotherapy developed a PTEN frameshift mutation. No molecular hints addressing resistance emerged in the remaining four patients with analyses performed. Tumour mutational burden, evaluated by WES in seven patients, was low (median = 2.06 mutations/megabase, range = 1.57–3.75 mut/Mb). Conclusions: Novel resistance mechanisms to BRAF/MEK inhibitors in BRAF V600E NSCLC were identified, pointing out the recurring involvement of the MAPK pathway and guiding the development of new treatment strategies. Highlights: Novel resistance mechanisms to BRAF/MEK inhibitors in BRAF V600E non–small cell lung cancer (NSCLC). Patients benefited from deep molecular analyses (targeted NGS, WES, RNAseq, CGH array) at progression to BRAF/MEK inhibitors. Acquired molecular mutations potentially responsible for resistance were MEK1 K57N, PTEN N329fs, NRAS Q61R and KRAS Q61R. These resistance mechanisms, restoring the MAPK pathway, overlap with the ones observed in different BRAF V600E cancers.